2003
DOI: 10.1080/13674580300200218
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Experiences of the Probation Period of Teaching in Kenya: implications for teacher induction policies and programmes

Abstract: The probation period for Newly Qualified Teachers (NQTs) in Kenya has hardly been studied. Universities have produced thousands of teachers, but it is not clear as to their experiences in schools. This study examines the experiences of graduate teachers during their probation period (first 2 years of service) in order to find out their expectations, surprises, difficulties and the extent of assistance received from mentors. Finally, teachers' suggestions for improvement of the induction process are examined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(5 reference statements)
0
5
0
1
Order By: Relevance
“…The research reveals that teachers who invited colleagues to observe their lessons made substantial changes in their teaching methodologies, as compared with teachers who did not have such opportunities. Furthermore, Indoshi (2003) indicates the problematic situation faced by novice teachers in Kenya, where the professional development of teachers has deteriorated due to lack of practice-oriented training in schools, which is supposed to be provided by senior mentors. All these studies demonstrate the importance of in-service teacher training, with special emphasis on practices in classrooms and collaboration with other teachers, in order to promote the professional development of teachers.…”
Section: Introductionmentioning
confidence: 98%
“…The research reveals that teachers who invited colleagues to observe their lessons made substantial changes in their teaching methodologies, as compared with teachers who did not have such opportunities. Furthermore, Indoshi (2003) indicates the problematic situation faced by novice teachers in Kenya, where the professional development of teachers has deteriorated due to lack of practice-oriented training in schools, which is supposed to be provided by senior mentors. All these studies demonstrate the importance of in-service teacher training, with special emphasis on practices in classrooms and collaboration with other teachers, in order to promote the professional development of teachers.…”
Section: Introductionmentioning
confidence: 98%
“…Studies in other contexts have suggested that the absence of any formalised induction programme for NQTs is detrimental to their development as teachers. (See, for example, the findings reported in this journal by Indoshi (2003) in the Kenyan context.) Scotland introduced a similar programme in 2002, followed by Wales in 2003.…”
mentioning
confidence: 84%
“…Since the early 1990s there has been a growing interest in the place of personal narrative and history in the development of teacher identity (Carter & Doyle, 1996), and it is a method adopted by several researchers who have published in this journal (see, for example, Indoshi, 2003). The narratives teachers construct to make sense of their experiences reflect how these experiences have become meaningful to their professional thinking and behaviour, their development of what Kelchterman (1999) identifies as a 'personal interpretive framework':…”
Section: Narrative-biographical Perspectivementioning
confidence: 99%
“…Moreover, it has been pointed out that in developing countries, INSET is not thorough in terms of changing the actual practices during lessons, and the follow-ups conducted on INSET are inadequate (O'Sullivan, 2002). In addition, there is a serious lack of collegiality in schools, which is detrimental to the professional development of teachers shortly after their induction (Indoshi, 2003).…”
Section: Introductionmentioning
confidence: 99%